Nomenclatural and taxonomic notes on some names of Sesleria sect. Argenteae (Poaceae) from Italy and the Balkans - Di Pietro, Romeo; Kuzmanović, Nevena; Lakušić, Dmitar; Viciani, Daniele; Fortini, Paola; Iamonico, Duilio (Phytotaxa, 2021)
Several names belonging to the Sesleria sect. Argenteae (Poaceae) were discussed in this paper and, where necessary, typified. Lectotypes were designated for the names Sesleria nitida var. brevidentata, S. nitida var. intermedia, S. nitida var. tenoreana f. macrostachya, and S. nitida var. tenoreana f. visianii. Neotypes were designated for the names Sesleria nitida var. tenoreana s.s. and S. nitida var. de-gasperiana. Synonyms were proposed for the following names (accepted names in brackets): S. feretrana (= S. italica), S. italica subsp. mariculensis (= S. italica), S. nitida var. brevidentata (= S. vaginalis), S. nitida var. candae (= S. italica), S. nitida var. intermedia (= S. robusta), S. nitida var. tenoreana f. visianii (= S. italica), and S. nitida var. tenoreana f. macrostachya (= S. italica). As regards Sesleria nitida var. de-gasperiana and S. nitida var. sancti-marinii, they were confirmed as synonyms of S. pichiana. Due to the extremely limited number of herbarium specimens available, we could not confirm the taxonomic autonomy of S. nitida var. pulchella (basionym of the taxon currently accepted as S. pulchella) and consider it as a preliminary synonym of Sesleria italica.